Gastric cancer during pregnancy with placental involvement: case report and review of published works - Seiya Oga; Masahiro Hachisuga; Nobuhiro Hidaka; Yasuyuki Fujita; Hiroshi Tomonobe; Hidetaka Yamamoto; Kiyoko Kato (Korean Society of Obstetrics and Gynecology, 2019)
Gastric cancer involving the placenta during pregnancy is rare; however, we present 1 such case in this report. A 31-year-old Japanese woman was referred at 26 weeks of gestation for the evaluation of a swollen left supraclavicular lymph node. Biopsy revealed poorly differentiated adenocarcinoma, and esophagogastroduodenoscopy with biopsy of the stomach confirmed the diagnosis of gastric cancer. Her epigastric and back pain became more pronounced and her general status worsened, and we performed a cesarean delivery at 29 weeks. Microscopic examination of the placental specimen revealed poorly differentiated adenocarcinoma cells diffused into the intervillous space. Postpartum chemotherapy consisted of S-1 plus oxaliplatin. Unfortunately, this treatment was ineffective, and the patient died 3 months after delivery. The infant did well, without clinical or laboratory manifestations of metastasis. In patients with advanced gastric cancer during pregnancy, it is important to perform a microscopic examination of the placenta to evaluate for metastatic involvement.